Caregiver Support in Mental Health Recovery: A Critical Realist Qualitative Research - Lauzier-Jobin, François; Houle, Janie (Qualitative Health Research, 2021)
Support from caregivers is an important element of mental health recovery. However, the mechanisms by which social support influences the recovery of persons with depressive, anxiety, or bipolar disorders are less understood. In this study, we describe the social support mechanisms that influence mental health recovery. A cross-sectional qualitative study was undertaken in Québec (Canada) with 15 persons in recovery and 15 caregivers—those having played the most significant role in their recovery. A deductive thematic analysis allowed for the identification and description of different mechanisms through a triangulation of perspectives from different actors. Regarding classic social support functions, several of the support mechanisms for mental health recovery were identified (emotional support, companionship, instrumental support, and validation). However, informational support was not mentioned. New mechanisms were also identified: presence, communication, and influence. Social support mechanisms evoke a model containing a hierarchy as well as links among them.